Eurocrime! : the Italian cop and the gangster films that ruled the 70s - Malloy, Mike, 1976-; Stielstra, Aaron; Subgenre Entertainment (Firm); Soundview Media Partners ([United States] : Subgenre Entertainment, LLC, 2012)
A documentary concerning the violent Italian 'poliziotteschi' cinematic movement of the '70s which, at first glance, seems like just a bunch of cheap rip-offs of American crime films like Dirty Harry or The Godfather. But on closer inspection, these films were really addressing distinctly Italian issues like the Sicilian Mafia and red terrorism.
Originally released as a motion picture in 2012.
Featuring interviews with: Franco Nero, John Saxon, Henry Silva, Antonio Sabáto, Luc Merenda, [and 16 others].
Narated by Aaron Stielstra.
Cinematographers, Federico Caddeo, Michael A. Martinez ; editor, Mike Malloy ; music, Calibro 35, Glows in the Dark, Aaron Stielstra, Chris Casey, Drew de Man, Mike Malloy.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 20, 2019)
Keywords: Crime films -- Italy -- History and criticism; Gangster films; Crime in popular culture -- Italy; Motion pictures -- Italy -- History and criticism; Violence in motion pictures; Police and motion pictures; Crime -- Italy; Violence -- Italy; Documentary films; Feature films; Nonfiction films; Historical films; Internet videos; Streaming video